Development of microstrip moisture sensor for grains - Jafari, Fariba; Khalid, Kaida; Wan Yusoff, Wan Mohd Daud; Hassan, Jumiah (Universiti Putra Malaysia Press, 2005)
Measuring moisture content is a very important process to produce good quality materials and products. The standard technique of measuring moisture content is oven-drying method. Knowing the moisture level of grain is important for harvest, transport, safety storage, selling price and etc. In this study, a microstrip sensor is developed to determine the optimum moisture content of grains based on microwave attenuation. It is a four layered semi-infinite microstrip structure: consists of RT-Duroid substrate, protective layer, wet medium, and air. It is a functional relation between the transmission characteristics and the wet media which is affected by the configuration and dimension of the sensor and the electric properties of the dielectric layers have been developed. Characteristic impedance and phase constant are two important transmission parameters which involved in this interaction. The propagation of the electromagnetic wave in the microstrip is based on Quasi-transverse electromagnetic mode. Computational Analysis is used to obtain these two parameters and mostly numerical method is applied to analyze the multilayer microstrip structure. The characteristic impedance and the effective dielectric constant are drastically affected by the thickness of the protective layer. Based on this planner structure it is suitable to determine moisture content of grain inside sack more efficiently with a greater accuracy.